Site-specific assessment of mechanical loads on photovoltaic modules from meteorological reanalysis data. (August 2019) - Camus, Christian; Offermann, Pascal; Weissmann, Martin; Buerhop, Claudia; Hauch, Jens; Brabec, Christoph J.
Graphical abstract: (a) Comparison of wind gust data collected at a DWD station in Dresden and data obtained from ERA interim and COSMO reanalysis data. (b) Electroluminescence image of a photovoltaic module damaged by mechanical loads. Black areas comprise electrically weakly connected areas which cannot contribute to power production anymore and result from the damage caused by the load. (c) Mechanical load set up at the ZAE Bayern, which can be used for simulating wind and snow loads with simultaneous detection of the generation and evolution of solar cell cracks in-situ by means of electroluminescence. Highlights: The method allows forecasting of PV module degradation for virtually any site in the world. Reanalysis is applied for PV degradation forecasting for the first time. The method can be transferred to other degradation factors. Site assessment and site-specific module design will benefit from this method. Excellent agreement between simulated and measured data is achieved. Abstract: This work demonstrates the capability of meteorological reanalysis data for estimating mechanical stresses due to wind gusts on photovoltaic modules. Besides the immediate power loss caused by the inactive solar cell areas within the module, the influence of cracks induced by such mechanical loads on the ageing and degradation behavior of PV modules is in the focus of current PV reliability research. To choose and/or design the optimum module for a given deployment site at the most economical cost, the mechanical loads the module will be exposed to during its service life need to be estimated. Hence, this paper introduces a new methodology for assessing and deducing site-specific mechanical load scenarios which are expected to be imposed on photovoltaic modules by wind gusts for a given location. The approach presented here is based on the linear calibration of meteorological reanalysis data with publicly available and standardized high-quality surface weather station data of local weather services. In this fashion, site-specific mechanical load scenarios can be deduced for virtually any site covered by the respective reanalysis data set. These scenarios can be used for developing site-specific module qualification tests, thereby providing a methodology enabling climate-specific module designs or specifications. This methodology can also be transferred to virtually any location and other climate and weather parameters such as snow loads, UV dose, etc. Hence a complete assessment of all weather-related degradation scenarios could be deduced eventually.